Enhanced energy management system for isolated microgrid with diesel generators, renewable generation, and energy storages - Manandhar, Ujjal (2024)
This paper presents an enhanced control and energy management strategy for the remote isolated power system. The presented control method includes the hybrid energy storage system control with a supercapacitor voltage restoration loop. This method improves the transient response and extends the battery lifespan while maintaining the SC voltage at a defined range of operation. To maximize the usage of renewable energy and reduce the diesel generator's frequent turn-on and off operation, the novel battery state of charge stop control is included in the energy management system. This improves the lifetime of diesel generators and reduces maintenance costs. In the proposed control method, a stabilizing control method is also introduced which helps in a seamless transition from grid-connected mode to islanded operating mode. The effectiveness of the proposed EMS and control method is validated by real-time simulation studies.